Gcn5p-dependent acetylation induces degradation of the meiotic transcriptional repressor Ume6p - Mallory, Michael J. (The American Society for Cell Biology, 2012)
Ume6p represses early meiotic gene transcription in Saccharomyces cerevisiae by recruiting the Rpd3p histone deacetylase and chromatin-remodeling proteins. Ume6p repression is relieved in a two-step destruction process mediated by the anaphase-promoting complex/cyclosome (APC/C) ubiquitin ligase. The first step induces partial Ume6p degradation when vegetative cells shift from glucose- to acetate-based medium. Complete proteolysis happens only upon meiotic entry. Here we demonstrate that the first step in Ume6p destruction is controlled by its acetylation and deacetylation by the Gcn5p acetyltransferase and Rpd3p, respectively. Ume6p acetylation occurs in medium lacking dextrose and results in a partial destruction of the repressor. Preventing acetylation delays Ume6p meiotic destruction and retards both the transient transcription program and execution of the meiotic nuclear divisions. Conversely, mimicking acetylation induces partial destruction of Ume6p in dextrose medium and accelerates meiotic degradation by the APC/C. These studies reveal a new mechanism by which acetyltransferase activity induces gene expression through targeted destruction of a transcriptional repressor. These findings also demonstrate an important role for nonhistone acetylation in the transition between mitotic and meiotic cell division.